2008
DOI: 10.1093/ndt/gfn682
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of low triiodothyronine according to the stage of chronic kidney disease in subjects with a normal thyroid-stimulating hormone

Abstract: This study showed that low T3 syndrome was highly prevalent in CKD and was a remarkable finding in early CKD. Furthermore, serum T3 levels were associated with severity of CKD even in the normal TSH level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
62
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 14 publications
12
62
0
1
Order By: Relevance
“…This study showed that low T3 syndrome was highly prevalent in CKD and was a remarkable finding in early CKD. Furthermore, serum T3 levels were associated with severity of CKD in normal TSH level (13).…”
Section: Resultsmentioning
confidence: 93%
“…This study showed that low T3 syndrome was highly prevalent in CKD and was a remarkable finding in early CKD. Furthermore, serum T3 levels were associated with severity of CKD in normal TSH level (13).…”
Section: Resultsmentioning
confidence: 93%
“…The difference between clinical and subclinical hypothyroidism is that in the subclinical type serum level of TSH is increased without the presence of the overt clinical manifestation of hypothyroidism. Similarly, the rate of "low T3 syndrome'' also referred as "the euthyroid sick syndrome" in patients with CKD increases consistently with declining GFR and it varies from 20% to 80% (100)(101)(102)(103). Euthyroid sick syndrome is the most common thyroid disorder in CKD patients.…”
Section: Ckd and Thyroid Diseasesmentioning
confidence: 99%
“…Recent reports suggest that as many as 70% of patients with ESRD present with low T3 levels (2)(3)(4)(5) and as many as 20%-25% have subclinical hypothyroidism (6,7). The underlying pathophysiology of these derangements is likely multifactorial, involving iodine retention, altered serum protein binding capacity, systemic inflammation, and peripheral deiodinase activity (8,9).…”
Section: Introductionmentioning
confidence: 99%